A Personalized Multifunctional 3D Printed Shape Memory‐Displaying, Drug Releasing Tracheal Stent. (13th September 2021) - Maity, Nabasmita; Mansour, Nicola; Chakraborty, Priyadarshi; Bychenko, Darya; Gazit, Ehud; Cohn, Daniel
Abstract: The ability to engineer custom‐made medical devices and to implant them minimally invasively are two important trends in modern surgery. The personalization of the device is achieved by 3D printing it, while the capacity to deploy it minimally invasively harnesses the shape memory behavior displayed by the inks used. This study introduces a 3D printed, shape memory‐displaying tracheal stent based on novel, flexible photo‐polymerizable inks comprising polypropylene glycol/polycaprolactone triblocks. This research introduces the in situ welding strategy, whereby thin and flexible layers of the stent are separately printed, sequentially deployed, and then welded together at the tracheal site. By doing so, the insertion profile of the device is dramatically reduced and its flexibility largely increased. Porous stents are 3D printed seeking to prevent mucus plugging. By combining more than one ink, their properties are further fine‐tuned. Polyethylene glycol chains are covalently bonded to the stent surface to minimize biofilm formation, an important drawback of current tracheal stents. The in vitro cell viability and cell adhesion behavior of the treated surfaces reveal their compatibility and anti‐adhesive behavior. In order to prevent implant‐related infections, ciprofloxacin is added to the ink, and released in vitro over time, rendering the stent with antibacterial activity. Abstract : Personalized 3D printed, shape memory‐displaying tracheal stents based on optimized polypropylene glycol/polycaprolactone crosslinkable inks, are developed. Using the in situ welding strategy, thin layers of the stent are independently printed, sequentially deployed, and then welded together. Different inks are used in the bulk and surface of the stent, further fine‐tuning its properties. The printed stents are also rendered with anti‐fouling and antimicrobial capabilities.